Study of Inkjet-Printed Silver Films Based on Nanoparticles and Metal-Organic Decomposition Inks with Different Curing Methods - Peng Xiao (Micromachines, 2020)
Currently, inkjet printing conductive films have attracted more and more attention in the field of electronic device. Here, the inkjet-printed silver thin films based on nanoparticles (NP) ink and metal-organic decomposition (MOD) ink were cured by the UV curing method and heat curing method. We not only compared the electrical resistivity and adhesion strength of two types of silver films, but also studied the effect of different curing methods on silver films. The silver films based on NP ink had good adhesion strength with a lowest electrical resistivity of 3.7 × 10−8 Ω·m. However, the silver film based on MOD ink had terrible adhesion strength with a lowest electrical resistivity of 2 × 10−8 Ω·m. Furthermore, we found a simple way to improve the terrible adhesion strength of silver films based on MOD ink and tried to figure out the mechanisms. This work offers a further understanding of the different performances of two types of silver films with different curing methods.